2012
DOI: 10.1080/0886571x.2012.642268
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Residential Treatment Outcomes for Emotionally and Behaviorally Disordered Youth: The Role of Pretreatment Factors

Abstract: This study examined outcomes with 170 children and youth admitted to residential treatment with complex mental health problems. Overall, outcomes at 2 years post-treatment was predicted by children and youth's behavioral pretreatment status reflected in lower internalizing and externalizing behavior at admission. These findings recognize a cluster of variables upon admission that are differentially predictive of specific outcomes. Higher school participation/achievement and an absence of witnessing interparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Even though the same training protocol was implemented, nontreatment variables might be account for such discrepancies. Evaluative studies of behavioral treatments (e.g., cognitivebehavioral therapy, parent training, residential treatment) have reported that various pretreatment factors (e.g., contextual variables, comorbidity, readiness to change) influence outcomes for children with ADHD (Beauchaine et al, 2015;den Dunnen et al, 2012;Jarrett, 2013). Neurocognitive training has revealed its own arena of promising effectiveness, which is different from behavioral treatment nor stimulus medication (for a review, see Chacko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the same training protocol was implemented, nontreatment variables might be account for such discrepancies. Evaluative studies of behavioral treatments (e.g., cognitivebehavioral therapy, parent training, residential treatment) have reported that various pretreatment factors (e.g., contextual variables, comorbidity, readiness to change) influence outcomes for children with ADHD (Beauchaine et al, 2015;den Dunnen et al, 2012;Jarrett, 2013). Neurocognitive training has revealed its own arena of promising effectiveness, which is different from behavioral treatment nor stimulus medication (for a review, see Chacko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that educational outcomes are not being sufficiently addressed within the residential treatment setting (Shabat et al, 2008), which is important as educational achievement prior to admission predicted post-discharge educational achievement (Den Dunnen et al, 2012). Furthermore, a recent Canadian study indicates poorer educational outcomes with a large proportion of youth not attending school between 1 and 2 years post-discharge (Preyde, Adams, Cameron, & Frensch, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A continuum of care typically offers a system of clinic-or home-and school-based outpatient visits, acute hospital options, and more intensive residential treatment, with varying degrees of integration or discontinuities depending on local resources and coordination. Residential treatment refers to the delivery of inpatient services in which children and youth reside away from their family homes (Den Dunnen et al, 2012;Stewart, Thornley et al, 2020). Residential services are generally considered after less intense outpatient interventions are tried and are intended to stabilize severe behavioral symptoms (James et al, 2010;Lyons, 2004).…”
Section: Introductionmentioning
confidence: 99%